Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1212/cpj.0000000000000982
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 “Sheltering in Place” on Activity in People With Multiple Sclerosis

Abstract: People with neurological conditions that impair mobility such as multiple sclerosis (MS) have low levels of physical activity, with walking their primary form of exercise. When the San Francisco Bay Area shelter-in-place order was announced in mid-March 2020 to flatten the curve of SARS-CoV-2 infections, the abrupt closure of gyms, fitness studios, and malls greatly limited options for safe exercise. We leveraged an ongoing study utilizing wearable technology, to understand the impact of the shelter-in-place p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…The cause is likely multifactorial. During the pandemic, many PwNID were no longer able to access resources such as community centers, gyms, public transportation, home care and rehabilitative services ( Block et al., 2021 ; Lebrasseur et al., 2021 ), and there may have been interruptions with access to infusion therapies for the 54.6% of patients who reported current infusion DMT therapy (Supplemental Table 4). These restrictions would likely have a greater adverse effect on those with pre-existing physical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The cause is likely multifactorial. During the pandemic, many PwNID were no longer able to access resources such as community centers, gyms, public transportation, home care and rehabilitative services ( Block et al., 2021 ; Lebrasseur et al., 2021 ), and there may have been interruptions with access to infusion therapies for the 54.6% of patients who reported current infusion DMT therapy (Supplemental Table 4). These restrictions would likely have a greater adverse effect on those with pre-existing physical limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerically, there did seem to be a slightly higher percentage of participants with progression in recent years, suggesting perhaps true change brought about by the pandemic. Reports on the effects of restricted outings on patient function during the pandemic are mixed: some but not all patients experienced clinically meaningful decreases in ambulatory activity 30 and physical function. 31 While some patients reported isolation and worse mood, others enjoyed the respite.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on remote activity monitoring showed that relatively small sample sizes were needed to detect a clinically meaningful difference in STEPS between treatment groups. 16,17 The objective of this study was to evaluate the association of structural central nervous system (CNS) pathology (MR imaging) with physical ambulatory disability (STEPS). The primary hypothesis was that spinal cord atrophy is a relevant anatomic substrate for STEPS, and therefore, spinal cord areas as well as brain deep and cortical GM volumes would correlate with STEPS.…”
Section: Association Of Daily Physical Activity With Brain Volumes An...mentioning
confidence: 99%
“…Furthermore, studies on remote activity monitoring showed that relatively small sample sizes were needed to detect a clinically meaningful difference in STEPS between treatment groups. 16 , 17 …”
Section: Introductionmentioning
confidence: 99%